Distribution of rs1801279 and rs1799930 Polymorphisms in NAT2 Gene among Population in Kupang, Nusa Tenggara Timur, Indonesia - Edhyana Sahiratmadja; Simeon Penggoam; Ani Melani Maskoen; Alvinsyah Adhityo Pramono; Dias Aryani; Nurul Setia Rahayu; Ramdan Panigoro (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: N-acetyltransferase-2 (NAT2) enzyme, encoded by NAT2 gene, plays a key role in metabolism of anti-tuberculosis (TB) drug isoniazid. Polymorphisms in NAT2 gene may result in different responses to TB therapy. Since TB prevalence in the eastern part of Indonesia is high, the aim of this study is to explore the distribution of NAT2 gene polymorphisms among population from Kupang, Nusa Tenggara Timur.METHODS: A total of 234 respondents were included from Kupang in 2012. Polymorphisms of NAT2 gene were examined using mass screening platform and the genotypes distribution were presented in percentage. To confirm NAT2 gene polymorphisms, polymerase chain reaction (PCR)-sequencing was performed in a subset of population.RESULTS: The polymorphisms of NAT2 gene showed that the distribution of rs1801279 for GG genotype was 100%; whereas the genotype distribution of rs1799930 for GG, GA and AA was 57%, 35.1% and 7.9%, respectively. In a subset of individuals (n13), acetylator status was well determined by PCR-sequencing, resulting in individual with wild type fast acetylator (NAT2*4; n4), intermediate (NAT2*4/*5 or NAT2*4/*6 or NAT2*4/*7; n7) and poor acetylators (NAT2*6/*6 or NAT2*7/*7; n2).CONCLUSION: The amino acid change in rs1799930 result in intermediate and poor acetylator status in Kupang population. This may lead to suboptimal response of TB therapy. Assessing acetylator status before TB therapy is important and may serve as personalized INH therapy.KEYWORDS: NAT2 gene, polymorphism, acetylator status, Kupang